PANDEMI COVID 19 SUATU PROBLEMA FAKTA SOSIAL KEHIDUPAN BUDAYA DAN KEBERAGAMAAN UMAT HINDU DI BALI - I Putu Gede Parmajaya (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
Hindus are people who are very obedient to all rules, prohibitions and laws (adat-state). This is because Hindus have been educated by their environment and social culture, through prarem (catur dresta) and awig-awig where the community lives, especially for the Hindu community in Bali whose religious life is governed by Balinese Hindu customs and culture. The outbreak and development of the COVID-19 pandemic is a social fact that is quite shocking to the religious life of Hindus in Bali. This is not without reason, because the continued outbreak of the COVID-19 pandemic has something to do with the social activities or religious rituals of Hindus in Bali, which are usually held in groups in one social community, starting from the sekaa, dadia and traditional village levels. In conclusion, Balinese Hindus must obey all orders including Hindu dogmas, government calls to implement dogmas and comply with various government programs such as social distancing, large-scale social restrictions (PSBB) or whatever form of prohibitions and recommendations must be carried out properly. This is so that Hindus in Bali can reorganize their lives to become more orderly (paradigm of social facts).